Migrations sanitaires et nouveaux enjeux autour la frontière lao-thaïlandaise - Audrey Bochaton (L'Espace Politique)
In this paper, we are exploring the current reorganisation of the Lao-Thai border area through the study of the therapeutic behaviours of individuals. We are focusing on the mobility of Laotian patients towards the neighbouring Thai hospitals. This practice of some border inhabitants can occur with the recent opening of Laos and it also emphasizes the development gap between the two countries. These patients’ flows are relevant indicators to describe and explain the socio-territorial processes currently at work within the Lao-Thai area. This approach using health determinants allows studying the various characteristics of a border: political, economic, social, cultural and medical. A disease does not only affect an individual in his biological body but it also has an impact on his family, his community, therapists, public health institutions as well as administrative and political institutions. Therefore, this approach offers us to embark in a new debate on the border.The Lao-Thai border area is complex; on the one hand, we observe the gradual weakening of the border though the practices of patients; and, on the other hand, its continuation is reaffirmed by statements of some political leaders and hospital officials on both sides.